Faktor-faktor Pendorong Penyebab Terjadinya Sistem Tallaqi Rukban Pada Komoditas Hasil Pertanian: Studi Kasus di Kabupaten Kerinci - Putra, Dontes; Azis, Saipul; Kamarni, Neng (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Tallaqi rukban is a buying and selling practice that is considered to violate Islamic business law. This practice is detrimental to one party, where the buyer buys the farmer's goods and deviates from the market price. This research is to determine the factors driving the practice of the tallaqi rukban system on agricultural commodities. This type of research is qualitative with a case study research approach. Primary data sources were obtained through interviews and observation methods. Based on the results of the study, the Tallaqi Rukban system still applies in some communities. The tallaqi rukban system, apart from being detrimental to village farmers, will also have an impact on market balance. The driving factors for the Tallaqi Rukban system in Kerinci are: Lifestyle; increased demand for goods; and Lack of knowledge of traders about the tallaqi rukban buying and selling system Keywords: Islamic Economics, Market Mechanism, Tallaqi Rukban.